Microbiology as an indicator of environmental health of Ilha Comprida lagoons- SP - Barbieri, Edison; Collaço, Fátima Lisboa; Doi, Sônia Assami [UNESP]; de Oliveira, Ana Julia Fernandes Cardoso [UNESP]; Rezende, Karina Fernandes Oliveira (Centro Universitario Sao Camilo - Sao Paulo, 2017)
With an area of 150 Km 2, the municipality of Ilha Comprida has limited sources of freshwater, sediments and nutrients. However, the sanitary aspects, aiming at Public Health, should be evaluated by determining the densities and the distribution of fecal pollution indicators, mainly bacteria from the group of thermotolerant coliforms. Thus, the objective of this work was to analyze the seasonal variations in the densities of thermotolerant coliforms in the lagoons of the municipality of Ilha Comprida (SP). For that, water samples were collected, in the period between 2014 and 2016, in lagoons of 13 localities (Juruvaúva, City Mar Sul, City Mar Norte, São Januário, Jardim Portugal, Atlântico, Icaraí, Adriana Sul, Adriana Norte, Porto Velho 2, Xandú, Jardim da Barra, Laguna Ponta da Praia) located in the municipality of Ilha Comprida (SP). The results showed that 21.90% of the samples were above the limit established by CONAMA. High densities of bacteria were found in the Icaraí lagoon. The highest averages of thermotolerant coliform densities were recorded in summer and spring. It is concluded that the seasonal variation interferes with the density of thermotolerant coliforms.
Microbiologia como indicador da saúde ambiental das lagoas de Ilha Comprida - SP
Keywords: Pollution; Public Health; Thermotolerant Coliforms; Water Quality